EFICIÊNCIA DE UM SISTEMA DE DESSALINIZAÇÃO DE ÁGUA SALOBRA UTILIZANDO ULTRAFILTRAÇÃO E OSMOSE REVERSA - Almeida, Juliano Penteado de (2017)
Considering the shortage of fresh water availability and an increased demand for water in the world, including Brazil, one of the alternatives for water supply are the water desalination system, which remove salts from brackish or seawater. The objective of this study was to evaluate the efficiency of treated water desalination system with production capacity of 1.0 m3 h-1 of treated water, installed in a water treatment plant of Sanepar (Water and Sanitation Company of the State of Parana), in Praia de Leste located in the coast of the state of Paraná, Brazil. In this study, the seawater was diluted with fresh water to make brackish water. The brackish water was prepared from the water mixture of the Pombas River, source of fresh water supply to the region, and sea water. The mixtures were performed to obtain concentrations of 1000 and 1500 mg L-1 of total dissolved solids (TDS). The system was composed of ultrafiltration (UF) as a pre-treatment to reverse osmosis (RO). Experiments were performed during 15 days for each TDS concentration of brackish water and TDS removal efficiencies were 99.0 and 99.1%, respectively. Besides TDS, other water quality parameters such as: electrical conductivity, turbidity, apparent colour, alkalinity, total hardness, calcium, magnesium, chlorides, sulphates and pH were monitored. Oxidation-reduction potential (ORP) and osmotic pressure, filtration rate and membrane recovery rate were also measured for the RO. The pilot plant system could remove all water quality parameters studied.